NATURAL LIGHTING COMPATIBILITY ANALISYS IN A SIMPLE HOUSE USING DIALUX SIMULATION - Ayu Setya Ningrum (Journal of Architectural Research and Education, 2022)
Research for this Journal investigate the compatibility of lighting in a simple house located in the Mangunreja sub-district, Tasikmalaya district. The aim is to evaluate the use of lighting whether it is effective or not according to SNI standards. Using special software will show whether there will be problems regarding the lighting in the residence and recommendations will be given to overcome them. This Journal can be useful for finding alternative solutions that can be applied in solving lighting problems in residential homes